Access to Power Politics and the Urban Poor in Developing Nations - Nelson, Joan M. (Center for International Affairs, Harvard University, 2017)
Joan Nelson elucidates the implications of this rapid growth and concomitant poverty for politics. Unlike many scholars who have sought an all-encompassing theory to explain the political behavior of the urban poor, Professor Nelson emphasizes the complex variety in the economic, social, and political circumstances that influence this behavior.Originally published in 1979.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905